STRATIGRAFIA E SEDIMENTOLOGIA DEI DEPOSITI FLUVIOLACUSTRI PLIO-PLEISTOCENICI DELL'AREA NORD OCCIDENTALE DEL VALDARNO SUPERIORE (TOSCANA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
In this paper are exposed the results of statigraphical and sedimentary analysis carried out in the north-western side of the Plio-Pleistocene fluviolacustrine upper Valdarno basin. The deposits of Montevarchi and Torrente Ciuffenna Successions were mapped. These deposits originated during the second and third phases, respectively, of a three-phases sedimentary history. They are separated by an erosional surface extended on the whole basin. According to the existing literature the chronostratigraphic gap extends from the upper part of the Early Pleistocene to the lower part of the Middle Pleistocene. The studied Successions can be classified using the unconformity-bounded stratigraphic units nomenclarure. The Sinthem term is proposed replacing the Succession term. The sedimentary evolution of the studied area is reconstructed starting from the Upper Pliocene. During the deposition of the Montevarchi Sinthem, a fluviolacustrine setting developed in this area. Facies analysis made it possible to recognize coarse-grained fan deltas prograding into a shallow lacustrine environment. The fan delta succession records significant tectonically induced variations of the clastic imput. The lower part of the fan delta succession is characterized by calcareous-arenaceous conglomerates of northwestern provenance. A subsequent rise of the Pratomagno chain lead to a predominance of arenaceous clastic material of eastern provenience. In the fan deltas deposits mammal fossils belonging to the Late Villafranchian and probably to the Early Galerian have been recovered. According ro these data the fluviolacustrine succession developed until the upper part of Lower Pleistocene. The unconformity separating the second and third phase may cover a smaller span of time in the studied area. In the third depositional phase an alluvial setting replaced the fluviolacustrine one previously developed. The alluvial fan succession building up the Torrente Ciuffenna Sinthem, filled the basin during the Middle Pleistocene. The erosion of the northern threshold closing the basin for the most part of the Pleistocene, induced in the Late Pleistocene the beginning of the erosive phase. On the whole the depositional evolution of the studied area was tectonically controlled. The climatic influence over the sedimentation was of lesser importance.
Keywords: Stratigraphy; Facies analysis; Fluviolacustrine deposits; Biochronology; Paleogeography; Upper Valdarno; Plio-Pleistocene.